Role of Recognition MicroRNAs in Hemaphysalis longicornis and Theileria orientalis Interactions - Jin Luo; Yangchun Tan; Shuaiyang Zhao; Qiaoyun Ren; Guiquan Guan; Jianxun Luo; Hong Yin; Guangyuan Liu (Pathogens, 2024)
Ticks are an important type of pathogen transmission vector, and pathogens not only cause serious harm to livestock but can also infect humans. Because of the roles that ticks play in disease transmission, reducing tick pathogen infectivity has become increasingly important and requires the identification and characterization of these pathogens and their interaction mechanisms. In this study, we determined the miRNA expression profile of Hemaphysalis longicornis infected with Theileria orientalis, predicted the target genes of miRNAs involved in this infection process, and investigated the role of miRNA target recognition during host–pathogen interactions. The results showed that longipain is a target gene of miR-5309, which was differentially expressed at different developmental stages and in various tissues in the control group. However, the miR-5309 level was reduced in the infection group. Analysis of the interaction between miRNA and the target gene showed that miR-5309 negatively regulated the expression of the longipain protein during the infection of H. longicornis with T. orientalis. To verify this inference, we compared longipain with the blocking agent orientalis. In this study, the expression of longipain was upregulated by the inhibition of miR-5309 in ticks, and the ability of the antibody produced by the tick-derived protein to attenuate T. orientalis infection was verified through animal immunity and antigen–antibody binding tests. The results showed that expression of the longipain + GST fusion protein caused the cattle to produce antibodies that could be successfully captured by ticks, and cellular immunity was subsequently activated in the ticks, resulting in a subtractive effect on T. orientalis infection. This research provides ideas for the control of ticks and tickborne diseases and a research basis for studying the mechanism underlying the interaction between ticks and pathogens.